A review of frailty instruments in human medicine and proposal of a frailty instrument for dogs - Melvin, Rachel L.; Ruple, Audrey; Pearson, Elizabeth B.; Olby, Natasha J.; Fitzpatrick, Annette L.; Creevy, Kate E. (Frontiers in Veterinary Science, 2023)
Over the last few decades, frailty has become a pillar of research and clinical assessment in human gerontology. This complex syndrome, characterized by loss of physiologic reserves leading to decreased resilience to stressors, is of critical importance because it predicts higher risks of poor health outcomes, including mortality. Thus, identifying frailty among the elderly human population has become a key focus of gerontology. This narrative review presents current scientific literature on frailty in both humans and animals. The authors discuss the need for an accessible frailty instrument for companion dogs suitable for general use in veterinary medicine and the advances that would be facilitated by this instrument. A phenotypic frailty instrument for companion dogs, utilizing components that are easily collected by owners, or in the general practice setting, is proposed. The authors elaborate on the domains (physical condition, physical activity, mobility, strength, cognitive performance, and mood and social relations), factors that will be included, and the data from the Dog Aging Project that inform each domain.